Hybrid Closed-Loop System Achieves Optimal Perioperative Glycemia in a Boy With Type 1 Diabetes: A Case Report - Dominguez-Riscart, Jesus; Buero-Fernandez, Nuria; Garcia-Zarzuela, Ana; Marmolejo-Franco, Fernando A.; Perez-Guerrero, Ana C.; Lechuga-Sancho, Alfonso M. (Frontiers in Pediatrics, 2021)
The goal in T1D therapy is to maintain optimal glycemic control under any circumstance. Diabetes technology is in continuous development to achieve this goal. The most advanced FDA and EMEA approved devices are HCL systems, which deliver insulin subcutaneously in response to glucose levels according to an automated algorithm. T1D is frequently encountered in the perioperative period. The latest international guidelines for the management of children with diabetes undergoing surgery include specific adjustments to patient’s insulin therapy, hourly blood glucose monitoring, and IV insulin infusion. However, these guidelines were published while HCL systems were still marginal. We present a case of a 9-year-old boy with long standing T1D, under HCL system therapy for the last 9 months, needing surgery for an appendectomy. We agreed with the family, the surgical team and the anesthesiologists, to continue HCL insulin infusion, without further adjustments, hourly BG checks or IV insulin, while monitoring closely. The HCL system was able to keep glycaemia within range for the total duration of the overnight fast, the surgery and the initial recovery, without any external intervention or correction bolus. This is, to the best of our knowledge, the first pediatric case reported to undergo major surgery using a HCL system, and the results were absolutely satisfactory for the patient, his family and medical team. We believe technology is ripe enough to advocate for a “take your pump to surgery” message, minimizing the impact and our interventions. Medical team may discuss this possibility with family and patients.